Pengembangan Video Pembelajaran Zat Adiktif Berbasis Kearifan Lokal untuk Mendukung Perkuliahan Kimia SMP - Dea Aninda; Masriani; Eny Enawaty (Postgraduate, University of Mataram, 2025)
This development research aims to assess the feasibility and responses to a local wisdom-based learning video on addictive substances as a learning resource for prospective junior high school Chemistry teachers. The ADDIE development model (analyze, design, develop, implement, evaluate) was used. Data were collected literature study, observation, interviews, and the use of feasibility instruments and response questionnaires. The video was validated by experts in material, language, and media aspects. Response questionnaires were conducted with 1 lecturer, 2 teachers, and 8 university students in a small-scale response questionnaires, and 36 university students in a large-scale response questionnaires. Feasibility results showed the video’s material was 100% feasible, language 94.6%, and media 100%, with an average of 98.2%. The average responses from lecturers and teachers were 100% and 99.2%, respectively, categorized as strongly good. University student responses were 87.6% in the small-scale response questionnaires, increasing to 92.4% in the large-scale response questionnaires, both categorized as strongly good. Therefore, the learning video on addictive substances based on local wisdom is highly suitable as a supporting resource for junior high school Chemistry and received strongly good responses from lecturer and teachers, and university students.